The identification and characteristics of salinity-related microRNAs in gills of Portunus trituberculatus - Lv, Jianjian (Cell Stress Chaperones, 2015)
MicroRNAs (miRNAs) are small noncoding RNAs that post-transcriptionally regulate gene expression in organisms. To understand the underlying mechanisms behind the molecular response of the crab to low salt-stress, high-throughput Illumina/Solexa deep sequencing technology was used to investigate the expression profiles of miRNAs under low salinity challenged. Two mixed RNA pool libraries of gill tissues from low salinity challenged (LC) and the control groups (NC) were sequenced on the Illumina platform. A total of 6,166,057 and 7,032,973 high-quality reads were obtained from the NC and LC libraries, respectively. Sixty-seven miRNAs consisting of 16 known and 51 novel ones were identified, among which, 12 miRNAs were differentially expressed in LC compared to NC. Thirty-four of the target genes predicted were differentially expressed in the opposite direction to the miRNAs, which were involved in crucial processes related to osmoregulation by gene ontology (GO) functional enrichment analysis, such as anion transport processes (GO:0006820) and chitin metabolic process (GO:0006030). These results provide a basis for further investigation of the miRNA-modulating networks in osmoregulation of Portunus trituberculatus. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12192-015-0641-9) contains supplementary material, which is available to authorized users.